The effectiveness of interasolve-book in improving learning independence and problem-solving skills of elementary school students - Deni Syahyadi; Fery Muhammad Firdaus; Sri Dewi Nirmala (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to test the effectiveness of using an interasolve-book as a learning medium in improving learning independence and problem-solving skills in elementary school students. Interasolve-book is an interactive book designed to stimulate students' critical thinking and problem-solving skills through engaging and relevant activities. The research method used is quantitative with a quasi-experimental design. The research subjects consisted of grade V students at SDN Handayani and SDN Rancabakti, which were used as an experimental group using an interasolve-book and a control group using conventional textbooks. A questionnaire measures learning independence, while a test measures problem-solving ability. The results show that using an interasolve-book significantly improves students' learning independence and problem-solving ability compared to conventional textbooks. This can be seen from the average score of students' learning independence and problem-solving ability in the experimental group, which was higher than that of the control group. The conclusion is that an interasolve-book can be an effective alternative learning medium to improve elementary school students learning independence and problem-solving skills. The implication of this study is the need for the development and application of interasolve-book in learning in elementary schools to improve the quality of education.